Inter-individual, inter-city, and temporal trends of per- and polyfluoroalkyl substances in human milk from Swedish mothers between 1972 and 2016. Issue 8 (10th July 2018) - Nyberg, Elisabeth; Awad, Raed; Bignert, Anders; Ek, Caroline; Sallsten, Gerd; Benskin, Jonathan P.
Abstract : Inter-individual, inter-city, and temporal trends (1972–2016) in PFAS concentrations were examined in human milk from Sweden. Abstract : Inter-individual, inter-city, and temporal trends of 19 per- and polyfluoroalkyl substances (PFASs) were investigated in human milk collected in Stockholm (1972–2016) and Gothenburg (2007–2015), Sweden. The concentrations of perfluorohexane sulfonate (PFHxS), perfluorononanoate (PFNA), perfluorodecanoate (PFDA), perfluoroundecanoate (PFUnDA), and perfluorotridecanoate (PFTrDA) in human milk from Stockholm increased significantly over the entire monitoring periods, whereas branched (Br) and linear (L) isomers of perfluorooctane sulfonamide (FOSA) decreased. In human milk from Gothenburg, significant downward trends were detected for perfluorododecanoate (PFDoDA), PFHxS and Br-perfluorooctane sulfonate (Br-PFOS) over the last decade. This declining trend was also observed for perfluorohexanoate (PFHxA), PFHxS, perfluorooctanoate (PFOA) and Br-PFOS in Stockholm over the same time period. No significant differences were observed in concentrations or relative PFAS profiles between Stockholm and Gothenburg. However, a comparison of the PFAS profile in Stockholm milk revealed distinct profiles for the time periods 1972–1996, 2000–2012, and 2013–2016, reflecting a shift in exposure over time. The lower bound estimated daily intake (EDI) for ∑PFAS concentrations in infants ranged from 7.1–40 ng per kg body weight per day (ng/kg bw/d) in Stockholm and from 5.2–25 ng/kg bw/d in Gothenburg over the studied time period, consistent with other European countries. Overall these data indicate that exposure to some legacy PFASs via breastmilk is declining, presumably as a result of regulation and phase-out initiatives. However, increasing concentrations for other PFASs and a shift in the overall PFAS profile in recent years may pose an ongoing health risk to infants.